An efficient and facile synthesis of 3-amino-5-chromenyl-butenolides from 3-formyl chromone, dialkyl acetylenedicarboxylate, and primary amines - Balalaie, Saeed; Ashouriha, Morteza; Rominger, Frank; Bijanzadeh, Hamid Reza (Molecular diversity, 2013)
A three-component reaction of 3-formyl chromones, dialkyl acetylenedicarboxylate, and isocyanides in the presence of $$\text{ POCl}_{3}$$was used as a highly efficient and practical approach for the synthesis of 3-amino-5-chromenyl-butenolides. High yields and high bond forming efficiency, and simple operations are the advantages of this method.